2012
DOI: 10.1021/pr300673x
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS Based Serum Metabolomics for Identification of Hepatocellular Carcinoma Biomarkers in Egyptian Cohort

Abstract: Although hepatocellular carcinoma (HCC) has been subjected to continuous investigation and its symptoms are well known, early-stage diagnosis of this disease remains difficult and the survival rate after diagnosis is typically very low (3–5%). Early and accurate detection of metabolic changes in the sera of patients with liver cirrhosis can help improve the prognosis of HCC and lead to a better understanding of its mechanism at the molecular level, thus providing patients with in-time treatment of the disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 36 publications
1
115
0
1
Order By: Relevance
“…The results indicated that patients with HCC had decreased LPCs, increased long-chain and decreased medium-chain acylcarnitines, and increased aromatic and decreased branched-chain amino acid [30]. UPLC-QTOF/MS and UPLC triple quadrupole linear ion trap MS approaches were performed on qualitative and quantitative comparisons of metabolite levels in sera of HCC patients and cirrhosis patients from Egypt [31]. The metabolites including GCA, GDCA, 3β,6β-dihydroxy-5β-cholan-24-oic acid, oleoyl carnitine and Phe-Phe were identified by UPLC-QTOF/MS.…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 99%
“…The results indicated that patients with HCC had decreased LPCs, increased long-chain and decreased medium-chain acylcarnitines, and increased aromatic and decreased branched-chain amino acid [30]. UPLC-QTOF/MS and UPLC triple quadrupole linear ion trap MS approaches were performed on qualitative and quantitative comparisons of metabolite levels in sera of HCC patients and cirrhosis patients from Egypt [31]. The metabolites including GCA, GDCA, 3β,6β-dihydroxy-5β-cholan-24-oic acid, oleoyl carnitine and Phe-Phe were identified by UPLC-QTOF/MS.…”
Section: Hepatocarcinoma (Hcc) Liver Cirrhosis and Chronic Liver Dismentioning
confidence: 99%
“…This phonotype was evidenced by the following metabolic changes including the decrease in glucose, citrate, and glycerol 3-phosphate but the increase in lactic acid and pyruvate [64][65][66][67][68][69]. On the other hand, the common induction of beta-oxidation was exemplified by the elevation of 2-oxoglutarate and reduction of free fatty acids, carnitine and carnitine esters [61,64,66,68,[70][71][72][73]. This theme will be further explored in the next section.…”
Section: Updates In Liver Cancermentioning
confidence: 99%
“…4 groups) rumen fluid dataset investigating the impact of altered diets of cows (Ametaj et al, 2010). The MS explores potential biomarkers of Hepatocellular Carcinoma in serum samples (Xiao et al 2012) and was accessed from the open source metabolomics data repository Metabolights (Haug et al, 2013) accession number MTBLS19.…”
Section: Real Datasetsmentioning
confidence: 99%